SEPARATION OF NATIONAL AND LOCAL ELECTIONS AFTER THE CONSTITUTIONAL COURT DECISION 135/2024: IMPLICATIONS FOR THE DURATION OF TENURE AND THE FILLING OF REGIONAL HEAD VACANCIES - Muhammad Didik Subiyanto; Sunardi; Isdiyana Kusuma Ayu (SOSIOEDUKASI, 2026)
The Constitutional Court Decision Number 135/PUU-XXII/2024 is present in response to the excessive burden of the 2024 simultaneous elections which interferes with the quality of democracy and the safety of organizers and voters. This research uses a juridical-normative method with a legislative and conceptual approach. The results of the study show that the juridical implications of this decision cause a time gap of about 2 to 2.5 years between the 2029 National Election and the 2031 Regional Election, which has the potential to cause a vacancy in the position of regional head. Legal measures that can be taken to overcome this vacancy include the appointment of the Acting Regional Head, strengthening the legitimacy and limits of his authority, comprehensive revision of the law, and the issuance of Perppu. The Constitutional Court emphasized that this separation does not reduce the fixed term of office for 5 years that has been regulated in the law. Thus, this decision ensures that the 2029 and 2031 elections are more manageable, efficient, and constitutional without harming the 1945 Constitution of the Republic of Indonesia.